FACTOR ANALYSIS ON WEATHER ELEMENTS THAT AFFECT MARINE TRANSPORTATION ACTIVITIES AT TANJUNG PERAK PORT WITH THE PRINCIPAL COMPONENT ANALYSIS METHOD - Nani Sunarmi; Weika Muchlis Aisyah; Uswatin Hasanah; Ayu Setiorini; Nur Lailatul Fitria; Frisca Karisma Wati (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
This research’s aim is to analyze weather elements that affect marine transportation activities at Tanjung Perak Port. The data used in this study is secondary data obtained from Meteorology, Climatology and Geophysics Agency of the Republic of Indonesia. The data used is weather element record from the meteorological station in Perak II Surabaya for the 2017-2021 period which includes variables of sunlight exposure, precipitation, humidity, wind direction, air pressure, wind speed, and air temperature. The method used is the Principal Component Analysis method. Based on the test, it is found that all weather variables can be analyzed using the Principal Component Analysis Method. The weather element variables formed 2 components which have Initial Eigenvalues 1. The first component consists of Air humidity, Precipitation, Sunlight exposure, and Air Pressure. The second component consists of Air Temperature, Wind Direction, and Wind Speed. Based on the two components formed, the first component is the most dominant component element that affects marine transportation activities at Tanjung Perak Port for the 2017-2021 period with Initial Eigenvalues of 3,681. And air pressure is the most dominant weather element with the loading value based on the Principal Component Analysis method is 0,867.